VD_FINDINFO ML / 2018 / 21 vom 22. März 2018 - VD Tribunal cantonal (2018)
MAINLEVÉE PROVISOIRE, TITRE DE MAINLEVÉE, ACTE DE DÉFAUT DE BIENS, CESSION DE CRÉANCECO | 165 CO, 149 al. 2 LP, 82 al. 1 LP, 82 LP